Justice delayed is growth denied: The effect of slow courts on relationship-specific industries in India - Amrit Amirapu (University of Kent, School of Economics, 2017)
Are well-functioning formal judicial institutions important for economic development, or can informal contracting arrangements provide adequate substitutes? This paper aims to answer this question using variation across industries in their reliance on contracts along with variation across Indian states in the average speed of courts. The identification strategy is motivated by theory from the incomplete contracting literature in which it is argued that transactions involving relationship-specific investments are more exposed to post-contractual opportunism and hence have greater need for efficient contract enforcement. The paper finds that the interaction between state level court efficiency and industry level relationship-specificity is highly predictive of future growth in India's formal manufacturing sector. The threat of omitted variable bias is minimized by the inclusion of state and industry fixed effects, while a number of robustness checks and placebo tests rule out competing explanations and provide additional confidence in the hypothesized mechanism.
Keywords: K40; O17; O43; 330; Courts; Legal Institutions; Contract Enforcement; Firms and Development